Rippling muscle disease: variable phenotype in a family with five afflicted members - Jacobi, Christian; Ruscheweyh, Ruth; Vorgerd, Matthias; Weber, Marc-André; Storch-Hagenlocher, Brigitte; Meinck, Hans-Michael (Muscle & nerve, 2010)
We report a family with rippling muscle disease (RMD) who had an autosomal dominant mode of inheritance. The father, mother, and one daughter proved to be heterozygous, and two sons were homozygous for the A92T mutation of the caveolin-3 gene. The cardinal features of RMD, particularly percussion-induced rapid contractions, muscle mounding, and muscle rippling, varied considerably among these subjects. Moreover, all examined individuals showed muscle weakness; however, the patterns were inconsistent. Muscle Nerve, 2010
First published: 20 August 2009
Gesehen am 11.07.2023